2002
DOI: 10.1034/j.1399-0004.2002.620206.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to 4‐chloro‐m‐cresol and caffeine in primary myotubes from malignant hyperthermia susceptible individuals carrying the ryanodine receptor 1 Thr2206Met (C6617T) mutation

Abstract: Malignant hyperthermia (MH) is an autosomal-dominant disorder of skeletal muscle, triggered by volatile anaesthetics and depolarizing muscle relaxants. The causative defect lies in the control of Ca(2+) release from the sarcoplasmic reticulum in skeletal muscle. Numerous mutations have been detected in the ryanodine receptor 1 (RyR1) gene, but so far an MH-causative role has only been confirmed for 16 human RyR1 mutations. In this report we show that myotubes derived from individuals carrying the RyR1 Thr2206M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Evidence of chronically elevated resting [Ca 2ϩ ] i has been presented on the basis of direct measurements with Ca 2ϩ -selective electrodes in isolated human and swine skeletal muscle fibers (28, 30). However, the extent to which high [Ca 2ϩ ] i contributes to sensitizing responses to caffeine and 4-CmC is not known.The purpose of the present study was to address the question of whether the enhanced intracellular Ca 2ϩ release at submaximal concentrations of caffeine and 4-CmC (44,45,48) in MHS cells is related to chronic elevation in resting [Ca 2ϩ ] i in affected muscle cells. To do so, resting [Ca 2ϩ ] i of MHS myoballs was decreased nearly to MHN levels by loading them with the Ca 2ϩ chelator 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid (BAPTA) and then reexamining the responses to caffeine and 4-CmC.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of chronically elevated resting [Ca 2ϩ ] i has been presented on the basis of direct measurements with Ca 2ϩ -selective electrodes in isolated human and swine skeletal muscle fibers (28, 30). However, the extent to which high [Ca 2ϩ ] i contributes to sensitizing responses to caffeine and 4-CmC is not known.The purpose of the present study was to address the question of whether the enhanced intracellular Ca 2ϩ release at submaximal concentrations of caffeine and 4-CmC (44,45,48) in MHS cells is related to chronic elevation in resting [Ca 2ϩ ] i in affected muscle cells. To do so, resting [Ca 2ϩ ] i of MHS myoballs was decreased nearly to MHN levels by loading them with the Ca 2ϩ chelator 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid (BAPTA) and then reexamining the responses to caffeine and 4-CmC.…”
mentioning
confidence: 99%
“…These clinical manifestations are associated with a nonphysiological elevation of myoplasmic Ca 2ϩ concentration ([Ca 2ϩ ]) at the cellular level ([Ca 2ϩ ] i ) (17,26). In addition, it was previously shown that skeletal muscle from MHS individuals and animals have a lower pharmacological threshold and an exaggerated response at submaximal concentrations of caffeine (22,45) and 4-chloro-m-cresol (4-CmC) (44,48) than do those with MH-nonsusceptible (MHN) muscle. This enhanced sensitivity is widely used as part of the clinical diagnosis of MH susceptibility in humans and has been confirmed experimentally in swine (16,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CMC is an agonist of ryanodine receptor type 1 (RYR1) located in the sarcoplasmic recticulum, causing release of Ca 2ϩ into the cytosol (41). The A549 cell line possess RYR1 (44), while recent studies have demonstrated specific use of CMC for stored calcium release in this cell line (30).…”
Section: Design Of Intracellular Oxygen Probes and Their Photophysicamentioning
confidence: 99%
“…Various methods have been developed to characterize the function of RYR1 variants: analysis of calcium release in human primary myotubes [Wehner et al, 2004[Wehner et al, , 2002Girard et al, 2002;Brinkmeier et al, 1999] and in immortalized B-lymphocytes from patients or after expression by transfection in various cell types [Yang et al, 2003;Girard et al, 2001;Censier et al, 1998;Tong et al, 1997], and determination of the channel openings in a ryanodine binding assay [Sambuughin et al, 2001]. Moreover, metabolic tests in vivo [Bina et al, 2006;Anetseder et al, 2003Anetseder et al, , 2002Textor et al, 2003] and in vitro [Klingler et al, 2002] have been developed to distinguish between MHS and MHN muscles.…”
Section: Introductionmentioning
confidence: 99%